2020
DOI: 10.1136/tobaccocontrol-2019-055136
|View full text |Cite
|
Sign up to set email alerts
|

The illicit cigarette market in six South African townships

Abstract: BackgroundWe estimate the size of the illicit cigarette market in low socioeconomic areas in South Africa before and after a tax increase. In 2018, the real excise tax increased by 3% and the value-added tax (VAT) rate increased from 14% to 15%. Thus, the real tax on cigarettes increased by 4%.MethodsA total of 2427 smokers were interviewed over two rounds of data collection (1234 before the tax increase and 1193 after). Data were collected in six townships across four of South Africa’s nine provinces. Smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Findings from our study confirmed that, as in the previous studies, older smokers [ 29 , 33 , 38 ], smokers who smoke more intensively [ 3 , 34 , 38 ] and have lower education [ 3 , 19 , 33 , 34 , 38 , 39 ] are more likely to use the illicit cigarettes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Findings from our study confirmed that, as in the previous studies, older smokers [ 29 , 33 , 38 ], smokers who smoke more intensively [ 3 , 34 , 38 ] and have lower education [ 3 , 19 , 33 , 34 , 38 , 39 ] are more likely to use the illicit cigarettes.…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of industry-funded studies conclude that there are some major issues regarding the quality of the estimates, including lack of methodological transparency; problems with data collection, analytical methods and result interpretation; and that they are not peer-reviewed [ 10 , 28 ]. Some studies show that industry-driven data exaggerate the extent of illicit trade [ 3 , 10 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It appears that our findings support this observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper is based on three standalone academic articles. [7][8][9] Table 1 provides a summary of the three articles, including sample sizes, years covered, data, results, advantages, disadvantages, and practical tips.…”
Section: Introductionmentioning
confidence: 99%